Comparison of Plaque Removal Efficacy of Modified Bass Technique and Charter’s Technique in Orthodontic Patients - Aneela Shabbir, Kawish Syed, Aimen Samreen Khan, Syeda Lalarukh Saba Shah, Ahmed, Nawal Noor, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To compare the efficacy of modified bass technique and charters technique in plaque removal among orthodontic patients. Study design: Single Blind Randomized control trial Place and duration of study: Department of Periodontology, Sardar Begum Dental College Peshawar from 1st July 2022 to 31st December 2022. Methodology: Forty six patients undergoing orthodontic treatment were enrolled. Patients were divided into two equal groups using lottery method. Group A used Modified Bass technique and Group B used Charter’s brushing technique. Plaque scores were measured by principal investigator and were recorded onthe Online Periodontal Chart of University of Berlin. Plaque score was recorded on all sides of the tooth in relation to bracket (mesial, distal, gingival, occlusal) using dental explorer after disclosing plaque by plaque disclosing tablet. Results: There were 24 (52.2%) females and 22 (47.8%) males. The mean plaque score for Group A was 25.76 and for Group B was 27.64, with no statistical difference after the test was applied. Conclusion: The modified Bass and Charters brushing techniques showed similar results in plaque removal efficacy. Scrubbing is the simplest and most often used cleaning procedure. Keywords: Plaque, Fixed appliances, Brushing techniques, Efficacy